Metazoan parasites of Clarias lazera Valenciennes, 1840 and Carassius carassius (Linnaeus, 1758) from Kepez I Hydro Electric Power Plant loading pond, Antalya, Turkey - (:unkn) unknown (My University, 2005)
0

In this study, metazoan parasites of Clarias lazera and Carassius carassius from Kepez I hydro-electric power plant loading pond were investigated. A total of 38 C. lazera and 89 C. carassius were studied. Fish samples were caught in May, August and November 2003 and February 2004. Quadriacanthus clariadis (Paperna, 1961) (Monogenea), Polyonchobothrium magnum (Zme'ev, 1936) (Cestoidea) and Orientocreadium sp. (Trematoda) were identified in C. lazera. Dactylogyrus vastator (Nybelin, 1924) (Monogenea) and Diplostomum sp. (Trematoda) were identified in C. carassius. Quadriacanthus clariadis and Polyonchobotrium magnum are the first record for Turkey.
Keywords: Balıkçılık; Zooloji